Pengaruh Islamic Branding dan Kualitas Pelayanan Islami terhadap Kepuasan Konsumen Kopontren Al Mubarok Cabang Kalisat Jember: Pengaruh Islamic Branding dan Kualitas Pelayanan Islami terhadap Kepuasan Konsumen Kopontren Al Mubarok Cabang Kalisat Jember - Hidayan, Nanda; Moh. Ainul Fikri; Ali, Misbahul (Al-Idarah, 2025)
The many types of retail in Indonesia certainly give rise to competition between retailers, so there needs to be an effective strategy to be able to compete with similar retailers, one of which is by creating consumer satisfaction through Islamic branding and Islamic service quality. This research uses a quantitative approach and the population of this research is all consumers of Kopontren Al Mubarok Branch Kalisat Jember. Data collection techniques were carried out using observation, questionnaires, interviews and documentation. Data analysis uses instrument tests, classical assumption tests, multiple linear regression analysis and hypothesis testing. The research results show that Islamic branding partially has a significant effect on consumer satisfaction at the Kopontren Al Mubarok Branch Kalisat Jember as proven by hypothesis testing which shows the tcount>ttable value (3.206>2.006) and the significance value is smaller than the specified significance level (0.002<0.05) . Islamic service quality partially has a significant effect on consumer satisfaction at the Kopontren Al Mubarok Branch Kalisat Jember, proven by hypothesis testing which shows the tcount>ttable value (2.620>2.006) and the significance value is smaller than the specified significance level (0.011<0.05). Islamic branding and Islamic service quality simultaneously have a significant effect on consumer satisfaction at Kopontren Al Mubarok Branch Kalisat Jember as proven by hypothesis testing which shows the Fcount>Ftable value (29.159>2.804) and the significance value is smaller than the specified significance level (0.000<0.05 ).